I would find a way - Big Mountain; Lindsey, Steve; Giant Records (United States : Giant Records, 1994)
Contains three tracks from the Giant album UNITY.
CD 1 : Single Edit / (4:05) -- Yo Lo Podria Hacer / (4:05) -- Album Version / (5:01).
Koleksi Khas Wiramanja.
Title from disc label.